Management of Anterior Chamber Dislocation of a Dexamethasone Implant - Nguyen, Thi Lyly; Wolfensberger, Thomas J. (Klinische Monatsblätter für Augenheilkunde, 2019)
Purpose To characterise the surgical removal technique of a dislocated dexamethasone implant in the anterior chamber and to gauge its success by analysing corneal transparency and subsequent visual acuity recovery in the postoperative phase.Methods Description of a patient who presented with an anterior chamber dexamethasone implant migration through an inferior iridotomy performed previously for a silicone oil fill in aphakia. Visual acuity had dropped to counting fingers due to marked corneal oedema.Results The implant was removed using a 23-g needle aligned with the axis of the implant through a paracentesis. After the clinical follow-up at 2 months, best-corrected visual acuity had returned to 0.2, which remained stable at the last follow-up at 14 months with an intraocular pressure of 10 mmHg. The corneal oedema resolved completely.Conclusion This novel surgical management of a dexamethasone implant dislocation into the anterior chamber was successful and resulted in no long-term corneal damage when the implant was removed without delay. A repeated Ozurdex injection in patients with previous inferior iridotomy may require prior suturing of the iridotomy.
Keywords: dexamethasone implant; anterior chamber migration; corneal oedema